Concise enantioselective synthesis of (R)-(+)-goniothalamin oxide, a trypanocidal active agent via L-prolinol catalyzed asymmetric epoxidation of cinnamaldehyde - Kumar, B. Senthil; Mandle, Ram D.; Kamble, Sanjay P.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2020)
A short and straight-forward enantioselective synthesis of (R)-(+)-goniothalamin oxide 2 has been achieved with an overall yield of 39% and 99% ee. The synthetic approach involves L-prolinol catalyzed asymmetric epoxidation of cinnamaldehyde followed by Lewis acid-mediated diastereoselective allylation of epoxy aldehyde as the key chiral-inducing steps.
Keywords: Allylation; asymmetric epoxidation; Esterification; Grubbs' catalyst; L-prolinol catalyst; Ring closing metathesis

P2O5-mediated Friedel-Crafts acylation of activated arenes with carboxylic acid as acylating agent - Kalshetti, Rupali G.; Mandle, Ram D.; Kamble, Sanjay P.; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2020)
P2O5 has been found to be a highly efficient and environmental friendly catalyst for the liquid-phase acylation of activated aromatic substrates giving aromatic ketones (45-93%) in a regioselective manner. Both aromatic and aliphatic carboxylic acids can be employed as acylating source. The process is particularly demonstrated at 100 g scale in the case of anisole and acetic acid to produce 4-methoxyacetophenone.
Keywords: 4-methoxyacetophenone; Carboxylic acid; Friedel-Crafts acylations; phosphorus pentoxide

Triethyl phosphite/benzoyl peroxide mediated reductive dealkylation of O-benzoylhydroxylamines: a cascade synthesis of secondary amides - Aegurla, Balakrishna; Mandle, Ram D.; Shinde, Prasad G.; Parit, Ratan S.; Kamble, Sanjay P.; Sudalai, Arumugam; Senthilkumar, Beeran (European Journal of Organic Chemistry, 2020)
A new triethyl phosphite/benzoyl peroxide (BPO) mediated system has been developed for the synthesis of secondary amides with good to excellent yields in a single step. This unprecedented cascade process involves sequential reduction of N-O bond and benzoylation followed by dealkylation of N-C bond ofO-benzoylhydroxylamines (O-BHA). The methodology is versatile as it tolerates a variety of aromatic and aliphaticO-BHA as substrates to access secondary amides.
Keywords: Amides; Cascade reactions; O-Benzoylhydroxylamines; Redox reactions; synthetic methods